2015
DOI: 10.5603/piap.2015.0073
|View full text |Cite
|
Sign up to set email alerts
|

Non-High Risk PE in the Patients with Acute or Exacerbated Respiratory Disease: The Value of the Algorithm Based on D-Dimer Evaluation and Revised Geneva Score

Abstract: Introduction: The diagnostic algorithm of non-high risk pulmonary embolism (PE) is based on probability scoring systems and plasma D-dimer (DD) assessment. The aim of the present study was to investigate the efficacy of Revised Geneva Scoring (RGS) and DD testing for the excluding of non-high risk PE, in the patients admitted to the hospital due to acute respiratory diseases. Material and methods:The consecutive patients, above 18 years of age, referred to the department of lung diseases, entered the study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…42 Clinical trials indicate that the significance of the revised Geneva score is primarily in the exclusion of PE combined with low D-dimer values. 43,44 The results of this study indicate that the revised Geneva score values did not influence physicians' decision not to refer such patients for further treatment, but only the D-dimer values. Analysis from other studies also implies underuse of clinical decision rules.…”
Section: Discussionmentioning
confidence: 68%
“…42 Clinical trials indicate that the significance of the revised Geneva score is primarily in the exclusion of PE combined with low D-dimer values. 43,44 The results of this study indicate that the revised Geneva score values did not influence physicians' decision not to refer such patients for further treatment, but only the D-dimer values. Analysis from other studies also implies underuse of clinical decision rules.…”
Section: Discussionmentioning
confidence: 68%
“…An important finding but of less diagnostic relevance in our case was the presence of raised d-dimer—these tests are known to commonly elevate in patients with respiratory symptoms and non-pulmonary embolism lung diseases such as malignancy, infection and COP. D-dimer assessments are thus most valuable when combined with probability scoring systems for thromboembolism and are useful to help rule out these conditions when not elevated due to their high negative predictive values10…”
Section: Discussionmentioning
confidence: 99%
“…4 It is worth to note that the increase in DD concentration may be also associated with neoplastic disease, vasculitis, as well as other inflammatory diseases. 5,6 Moreover, elevated DD levels are reportedly associated with higher risk of mortality. 6 Several studies confirmed an association between DD and tumour stage, lymph node involvement, and overall survival in patients with solid tumours, such as lung cancer, breast cancer, oesophageal cancer, gastric cancer, colon cancer and gynaecological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“… 4 It is worth to note that the increase in DD concentration may be also associated with neoplastic disease, vasculitis, as well as other inflammatory diseases. 5 , 6 Moreover, elevated DD levels are reportedly associated with higher risk of mortality. 6 …”
Section: Introductionmentioning
confidence: 99%